Meningkatkan Pelayanan Konsumen Melalui Critical Perseption Point (CPP) - Agung Tri Retnowati (Jurnal Computech & Bisnis (e-Journal), 2018)
Business competition in retail business today has become the focus of every entrepreneur. This happens with the continued development of business and business methods that can not be dammed. More sophisticated technology in the implementation can be balanced with consistency in the service, the norm makes consumers feel comfortable cost in store. To focus more on the things required by consumers, it is necessary to make a special location to get more specific problems. CPP determination (Critical Perception Point) is very useful to assist staff in providing optimal service to consumers. Standard Service with CPP can be used to improve customer satisfaction survey which is issued compared to previous year. Keyword : CPP, Consumer Sevice.